Functional and structural changes in the visual pathway in multiple sclerosis - María Carcelén‐Gadea; Carlos Quintanilla‐Bordás; Alicia Gracia‐García; Carolina García‐Villanueva; Nicolás Jannone‐Pedro; Lourdes Álvarez‐Sánchez; Laura Vilaplana‐Domínguez; Trinidad Blanco‐Hernández; José Miguel Pons‐Amate; Angeles Cervelló‐Donderis (Brain and Behavior, 2019)
Abstract Introduction Multiple sclerosis (MS) is a heterogeneous disease with an unpredictable course. Visual pathway is a target of the disease and may reflect mechanisms that lead to disability. Structural and functional changes in the visual pathway may be studied by noninvasive techniques such as optical coherence tomography (OCT), visual evoked potentials (VEP), or B‐mode transorbital sonography (TOS). Objectives The aim is to assess changes in the visual pathway in eyes of MS patients with and without a history of optic neuritis over a 3‐year period and to explore their relationship with disability. Materials and Methods In total, 112 eyes from 56 patients with relapsing MS were recruited: 29 with, and 83 without a history of ON (hON and nhON, respectively). Several parameters were measured by OCT, VEP, and TOS. Baseline measurements were also compared to 29 healthy controls. At 36 months, measurements were repeated in all eyes. Results At baseline, all tests showed significant differences in optic nerve structure and function in both patient cohorts in all the parameters studied, suggestive of more impairment of the visual pathway among the hON cohort. OCT showed significant differences between healthy controls and the nhON cohort. At 36 months, the nhON cohort showed significant changes by OCT, VEP, and TOS suggestive of further visual pathway impairment. OCT measurements also correlated with baseline EDSS among the nhON cohort. Conclusions OCT is the most suitable technique and outperforms VEP and TOS to detect subclinical damage in the visual pathway. It discriminated MS patients from healthy controls and showed a progressive decline in optic nerve thickness over time among these patients.